Analysis of the influence of learning video media on science process skills - Novilia, Novilia Mita Sari (Jurnal Ilmiah BioSmart (JIBS), 2021)
The purpose of this study was to determine the effect of instructional videos on science process skills (KPS). This type of research uses the Research and Development (R&D) research design and the ADDIE development model. This study uses one class as the experimental class. Methods of data collection using a pretest and posttest. Based on the results of the data obtained, the highest increase in students 'science process skills was in the fifth indicator, namely communicating with a percentage of 69%, this was in accordance with the results of the students' pretest and posttest obtained as well. Whereas for the lowest increase indicator, namely the third indicator grouped with a percentage of 17%. The overall average of learning videos can improve 27.3% of process skills. In conclusion,